2010
DOI: 10.1016/j.snb.2010.09.002
|View full text |Cite
|
Sign up to set email alerts
|

NO2 sensing properties of macroporous In2O3-based powders fabricated by utilizing ultrasonic spray pyrolysis employing polymethylmethacrylate microspheres as a template

Abstract: Macroporous (mp-)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…Second, the synergistic combination of the spherical and onedimensional carbon-based templates provides precise control over the interconnectivity and multimodality of the pores. Efforts to enhance the macroporosity by introducing spherical templates have been reported, [41][42][43] but the nanoscale point contacts between the spherical pores often limits the mass transport through such pores, as evidenced by the present 2M-SnO 2 -based sensor. The main breakthrough of the present study is the significantly enhanced interconnectivity between the different pore types, which was achieved by employing highly connecting, one-dimensional, carbon-based precursors, such as MWCNTs.…”
Section: Gas-sensing Characteristicsmentioning
confidence: 92%
“…Second, the synergistic combination of the spherical and onedimensional carbon-based templates provides precise control over the interconnectivity and multimodality of the pores. Efforts to enhance the macroporosity by introducing spherical templates have been reported, [41][42][43] but the nanoscale point contacts between the spherical pores often limits the mass transport through such pores, as evidenced by the present 2M-SnO 2 -based sensor. The main breakthrough of the present study is the significantly enhanced interconnectivity between the different pore types, which was achieved by employing highly connecting, one-dimensional, carbon-based precursors, such as MWCNTs.…”
Section: Gas-sensing Characteristicsmentioning
confidence: 92%
“…Shimizu and coworkers (Hieda et al 2008 ;Hayashi et al 2009 ;Morio et al 2009 ;Hyodo et al 2010 ) have shown that, by using a modi fi ed sol-gel technique, pyrolysis or a physical vapor deposition process employing a polymethylmethacrylate (PMMA) microsphere fi lm as a macropore template, macroporous ( mp -) fi lms of various materials promising for gas sensor application can be fabricated. They established that different kinds of gas sensors fabricated with the mp -semiconductor fi lms (SnO 2 and In 2 O 3 to detect H 2 , NO X , and H 2 S), photoluminescence-type (SnO 2 mixed with Eu 2 O 3 to detect H 2 and NO 2 ), and quartz crystal microbalance type (BaCO 3 to detect NO 2 ) showed stronger gas responses as well as fast response and recovery speeds in comparison with those fabricated with a conventional fi lm and powders without macropores (Hayashi et al 2009 ;Yuan et al 2011 ;Hyodo and Shimizu 2011 ) .…”
Section: Mesoporous Macroporous and Hierarchical Metal Oxide Structmentioning
confidence: 99%
“…Most reports found in recent literature on gas sensors for NO 2 , focus mainly on the study of WO 3 [18], ZnO [19] and SnO 2 [20,21] compounds, whether in the form of thin films or nanostructures prepared by various methods; and a smaller amount of work addressed to study other sensor compounds, such as In 2 O 3 [22]. With respect to cerium oxide as gas sensor there are few studies available in the literature; mostly using ceria as additive.…”
Section: Evaluation Of Sensor Propertiesmentioning
confidence: 99%